Immunogenicity and Safety of a Tetravalent Dengue Vaccine Administered Concomitantly or Sequentially With Tdap Vaccine: Randomized Phase IIIb Trial in Healthy Participants 9–60 Years of Age in the Philippines. Issue 9 (10th June 2021) - Santos, Jaime; Montellano, May Emmeline; Solante, Rontgene; Perreras, Nicole; Meyer, Stéphanie; Toh, Myew-Ling; Zocchetti, Céline; Vigne, Claire; Mascareñas, Cesar
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Incorporating dengue vaccination into existing childhood vaccination programs could increase vaccine coverage. This study assessed the safety and immunogenicity of concomitant versus sequential administration of the combined tetanus toxoid, reduced diphtheria toxoid and acellular pertussis (Tdap) vaccine and the tetravalent dengue vaccine (CYD-TDV). Methods: This phase IIIb, randomized, open-label, multicenter study was conducted in the Philippines in individuals 9–≤60 years of age (NCT02992418). Participants were to receive 3 CYD-TDV doses 6 months apart, the first dose administered either concomitantly or sequentially (28 days post-Tdap). Antibody levels were measured at baseline and 28 days post-first doses of Tdap vaccine and CYD-TDV, using enzyme-linked immunosorbent assay (pertussis, tetanus), micrometabolic inhibition test-toxin neutralization assay (diphtheria) and plaque reduction neutralization test (dengue). Immunogenicity was assessed for all participants, and statistical analysis reported for baseline dengue seropositive participants. Safety was assessed throughout. Results: Among 688 randomized participants, 629 (91.4%) were baseline dengue seropositive (concomitant group, n = 314 and sequential group, n = 315). After the first dose, non-inferiority of immune responses between concomitant and sequential vaccination was achieved; between-group geometric mean antibody concentration ratios were close to 1 for anti-PT, anti-FHA, anti-PRN and anti-FIM, between-group differences in percent achieving seroprotection (titers ≥0.1 IU/mL) were 0.26% (diphtheria) and 0.66% (tetanus), and between-group geometric mean antibody titer ratios were close to 1 for dengue serotypes 1–4. Safety profiles in both study groups were comparable. Conclusions: CYD-TDV and Tdap vaccine administered concomitantly or sequentially in baseline dengue seropositive participants elicited comparable immunogenicity and safety profiles.